The use of a jaw-designed suture passer as compared to the Lasso-loop suture technique for arthroscopic treatment of chronic lateral ankle instability - Weiwei Mao; Zhigao Jin; Yong Zhang; Wei Li; Ying Zhu; Weiqi Kong; Ying Wang; Jianzhong Qin (Journal of Orthopaedic Surgery)
Purpose This study compares the clinical outcomes of the Lasso-loop and Jaw-designed suture passer techniques for arthroscopic treatment of chronic lateral ankle instability (CLAI) caused by anterior talofibular ligament (ATFL) injuries. We aimed to assess whether the Jaw-designed technique provides similar outcomes with reduced intraoperative stitch time. Methods This retrospective cohort study included 40 patients with CLAI, who underwent arthroscopic ligament repair between February 2019 and February 2022. They were divided into two groups: 20 treated with the Lasso-loop technique and 20 with the Jaw-designed suture passer. Functional outcomes were evaluated using the American Orthopaedic Foot and Ankle Society (AOFAS) scale, Karlsson Ankle Functional Score (KAFS), Tegner activity scale (TAS), and Visual Analog Scale (VAS) for pain. Intraoperative ligament stitch time was also recorded for both groups. Results Both groups showed significant improvement in AOFAS, KAFS, TAS, and VAS scores from preoperative to final follow-up ( p < .001). The mean intraoperative ligament stitch time was significantly shorter in the Jaw-designed group (9.1 min) compared to the Lasso-loop group (16.5 min) ( p < .001). However, no significant differences in final functional outcomes (AOFAS, KAFS, TAS, and VAS scores) were observed between the two groups ( p > .05). Conclusion The Jaw-designed suture passer technique for repairing the ATFL in CLAI offers clinical outcomes comparable to the Lasso-loop technique, with the added benefits of a shorter suture time and simpler execution. This technique may be particularly beneficial for novice surgeons and can serve as a reliable alternative to the Lasso-loop suture technique in the arthroscopic repair of CLAI.